Preface: Special Issue on New Developments in Mathematical Programming and Operations Research - Dai, Yu-Hong; Han, De-Ren; Wu, Ling-Yun; Xu, Yan (Journal of the Operations Research Society of China (Internet), 2022)
Optimization and operations research in mitigation of a pandemic (Cai-Hua Chen, Yu-Hang Du, Dong-Dong Ge, Lin Lei, Yin-Yu Ye): This paper discusses several applications of supply chain management, public resource allocation, and pandemic prevention using optimization and machine learning methods. Augmented Lagrangian methods for convex matrix optimization problems (Ying Cui, Chao Ding, Xu-Dong Li, Xin-Yuan Zhao): This paper provides a gentle introduction to the recent advances in augmented Lagrangian methods for solving large-scale convex matrix optimization problems (CMOP), and reviews two types of sufficient conditions for ensuring the quadratic growth of a class of constrained CMOP which are regularized by nonsmooth spectral functions, along with the R-superlinear convergence of the Karush–Kuhn–Tucker (KKT) residuals. Game theory and the evolution of cooperation (Bo-Yu Zhang, Shan Pei): This paper introduces related static and dynamic game methods and reviews two types of mechanisms that can promote cooperation in groups of genetically unrelated individuals, (i) direct reciprocity in repeated games and (ii) incentive mechanisms such as reward and punishment.